Nilai-Nilai Pendidikan dalam Kitab Ummul Barahin Perspektif Imam Sanusi - Basirotun Nafidah; Wildan Habibi (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
The Book of Umm Barahin is the opus of Imam Sanusi which is one of the books in the field of aqidah which is famous among the scholars of Ahlussunnah wal Jama'ah. The book of Ummul Barahin is a book of monotheism which explains the Oneness of Allah and His attributes and the characteristics of His Messengers. The interesting thing about this book is the method of delivering the contents of the book by Imam Sanusi which is in accordance with the learning methods commonly used in the world of education. This thesis is studied using a qualitative approach and the type of research is library research. The concept of education in the Book of Umm Barahin Imam Sanusi's perspective includes the law of reason, the attributes of Allah and the evidence, the characteristics of the Apostles and their evidence, and the explanation of the creed. The methods used by Imam Sanusi in conveying the contents of his book are tabyin, rational, comparative, question and answer methods, stories method, and model method.